Purchase behavior in COVID-19 (2020)
This article explores the critical factors of consumption in Mexico, Ecuador, and Colombia, due to confinement and social distancing. Besides, which are the factors that influence the purchase decision. In the proposed model, we tested from quantitative research with a sample of 2,065 online consumers. We analyzed the following statistics: CFA, structural equations, invariance of measurement instruments, and multi-group analysis with the Smart Pls 3 and EQS 6.3 software. The study reveals that time, space, and place in the consumption process is more visible in the purchasing behavior with social distancing, healthy distance, and the commercial restriction caused by the health contingency. In addition to being a health and humanitarian crisis, the pandemic has severe economic consequences worldwide as 1) the increase in unemployment rates, 2) collapsed health systems, 3) education models overwhelmed by technology, 4) supply chains interrupted by the closure of borders, 5) international and domestic tourism suspended due to a lack of sanitary protocols,6) social coexistence curtailed by significantly increased infections and 7) a decreasing demand by consumers for the closure of companies. Despite being Latin American countries, cultural differences were not the priority of consumption in the crisis period due to Covid-19. They significantly change purchasing behaviors, and all have adapted to online and home delivery purchases by the social factor, local consumption, and consumers' attitude. The article presents several considerations on the main factors of consumption in Covid-19 in collectivist countries (North American and South America) such as Mexico, Colombia, and Ecuador and finds no substantial differences with consumers. There are practical implications for companies to adopt online channels and to create sales strategies in the face of the endemic pandemic.